Chat with our AI personalities
To do this equation, you collect like terms. 7x-4x+x-15 is your original equation, you have 3 terms with "'x'" in them, and they are 7x, -4x, and x. 7x + (-4x) +x simplifies to 4x, because 7-4 = 3 + 1 = 4 (the x is really 1x....). After this, you get 4x-15, which is as simplified as this equation can be.
Restate the question: Simplify: (x-3) + 4x(x-3) + 4x = x - 3 + 4x= x + 4x -3= 5x -3=======Answer 1:x - 3 + 4xThat expression is not an equation. It's just a number. The number dependson what the value of 'x' happens to be at the moment, and if 'x' changes, then(x - 3 + 4x) immediately changes. Without an equation, there's no "solution".Your expression would be an equation if there were an 'equals' sign ( = )anywhere in it.
3
If the equation is 4x - 10 = 36, then x = 9.
The value of x in the equation -2 x plus 3 4x-3 is 3.